Pengembangan Media Pembelajaran Trainer Mikrokontroller Atmega 16 Di Program Studi Pendidikan Vokasional Teknik Elektro - Nana Supriyana; Endi Permata; Mohammad Fatkhurrokhman (Jurnal Taman Vokasi, 2019)
Â Abstracts. This study aims to determine the design, performance and feasibility of developing microcontroller learning media on microcontroller courses in the Electrical Engineering Vocational Education Study Program. This type of research uses research and development (R&D) with the ADDIE development model from Robert Maribe Branch. The results of this study are: microcontroller learning media design, equipped with guidelines in the form of a jobsheet. Media specifications with a size of 80x60 cm, input components in the form of various sensors namely temperature sensors, ultrasonic sensors, PIR sensors, LDR sensors, fire sensors, and rain sensors, output components such as LCD 16x2, 5Vdc relays, LEDs, 220V lamps, servo motors, seven common anode segments, seven segment cathodes and 16x64 dot matrix. The process component is the minimum system using Atmega 16 and is programmed in Arduino Uno software, the performance of microcontroller learning media development in this learning process is so that students are able to operate various input or output components in the learning media, assessing the development of learning media with theory (Mardapi , 2012) .. based on the assessment of instructional media experts obtained an assessment that is "Very Eligible" with a percentage of 82%, while from the material experts on the development of media learning obtained an assessment of "Very Eligible" with a percentage of 78% and an average user rating of 76 categories " Very Worthy ". The effectiveness of the microcontroller Trainer learning media gets a value of "Very Effective" from the calculation of n-gain 0.76.